Perlindungan Konsumen Produk Skincare Pada Penjualan Secara Online - Otih Handayani; Esther Masri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Skincare is a skin care product that is popular among the majority of female consumers. One way to obtain skincare products is through online purchases, which, despite its advantages, also has disadvantages such as not meeting expectations (cheap prices but containing harmful substances) and being prone to fraud. The aim of this research is to understand the regulations regarding online buying and selling and consumer protection for skincare products using the online buying and selling system, particularly in terms of negative impacts on consumer health. This research is a doctrinal study that utilizes primary, secondary, and tertiary legal sources. The results of this research are as follows: Firstly, the online buying and selling of skincare products through marketplaces, as stipulated in Articles 1457 and 1458 of the Civil Code, utilize electronic contracts that include the identification of the parties involved, object and specifications, requirements for electronic transactions, pricing and costs, cancellation procedures, rights of aggrieved parties, and dispute resolution. Online buying and selling is recognized as a legitimate and accountable electronic transaction based on Government Regulation Number 71 of 2019 on the Implementation of Electronic Systems and Transactions. Online buying and selling is also regulated by the fatwa of the National Sharia Council of the Indonesian Ulema Council, No. 05/DSN-MUI/IV/2000, which provides provisions regarding payment, goods, parallel salam, goods delivery, cancellation, and disputes. Secondly, consumers of skincare products through online buying and selling are protected by the state both preventively through legislation (Consumer Protection Law No. 8 of 1999, Health Law No. 36 of 2009, Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Electronic Information and Transactions, Civil Code, and Criminal Code) and repressively (compensation by businesses; non-litigation through the Consumer Dispute Settlement Board (BPSK); litigation through the courts).